A comparison of different depth ablations in the treatment of painful bullous keratopathy with phototherapeutic keratectomy. Issue 8 (1st August 2001) - Maini, Raj; Sullivan, Laurence; Snibson, Grant R; Taylor, Hugh R; Loughnan, Michael S
Abstract : AIM: To study the efficacy of phototherapeutic keratectomy (PTK) for pain relief for patients with painful bullous keratopathy and poor visual potential. METHODS: Patients with painful bullous keratopathy and poor visual potential were treated with superficial PTK (8–25 μm), intermediate (50–100 μm) or deep PTK (25% stromal thickness) using the Nidek EC5000 excimer laser after manual epithelial debridement. Follow up ranged from 1 to 24 months (mean 6.5 months). Outcome measures included symptomatic relief and need for further treatment. RESULTS: In the superficial PTK group five of eight (62%) patients improved symptomatically after treatment. The three (38%) who did not improve went on to have penetrating keratoplasty for pain relief. In the intermediate depth group only two of five (40%) patients had symptom alleviation. The three others (60%) required further procedures. 20 of 24 (83%) patients treated with deep PTK had significant or total alleviation of symptoms. Of these, one developed acute anterior uveitis 9 months after PTK and two required botulinum ptosis for persistent corneal epithelial defects, one of whom had three consecutive episodes of microbial keratitis. Three of 24 suffered occasional discomfort and one patient required a penetrating keratoplasty for continued pain. CONCLUSION: PTK can be a useful therapeutic measure in painful bullous keratopathy with poor visual potential. Deep PTK appears to be more successful in pain management than superficial treatment.